2021
DOI: 10.1021/acs.jafc.1c05599
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antihypertensive Mechanisms of the Egg White-Derived Peptide QIGLF in Spontaneously Hypertensive Rats Revealed Using Untargeted Serum Metabolomics

Abstract: The angiotensin-converting enzyme (ACE) inhibitory peptide QIGLF derived from egg white was shown to have significant in vivo antihypertensive effects in our previous study, but the intervention mechanisms at the metabolic level are still unclear. The UPLC-QTOF/MS-based untargeted metabolomics approach was used to clarify the potential antihypertensive mechanisms of QIGLF in the serum of spontaneously hypertensive rats (SHRs). Multivariate statistical analysis showed a clear difference in the metabolite profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Hypertension is a major risk factor for cardiovascular diseases, affecting more than 20% of adults and causes about 19% of deaths worldwide (Yu et al ., 2021a, 2021b; Wu et al ., 2022). Angiotensin‐converting enzyme (ACE) is considered a key target for treating hypertension, and many ACE inhibitors have been developed to lower blood pressure, such as captopril and lisinopril (Yu et al ., 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is a major risk factor for cardiovascular diseases, affecting more than 20% of adults and causes about 19% of deaths worldwide (Yu et al ., 2021a, 2021b; Wu et al ., 2022). Angiotensin‐converting enzyme (ACE) is considered a key target for treating hypertension, and many ACE inhibitors have been developed to lower blood pressure, such as captopril and lisinopril (Yu et al ., 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a major risk factor for cardiovascular diseases, affecting more than 20% of adults and causes about 19% of deaths worldwide (Yu et al ., 2021a, 2021b; Wu et al ., 2022). Angiotensin‐converting enzyme (ACE) is considered a key target for treating hypertension, and many ACE inhibitors have been developed to lower blood pressure, such as captopril and lisinopril (Yu et al ., 2021a, 2021b). However, these synthetic ACE inhibitors have been reported to still not control blood pressure effectively and even have serious side effects on human health, including headache, fatigue, dry cough, angioedema and hyperkalaemia (Liu et al ., 2021; Xu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total amount of 613 kidney metabolites were detected in this study, and multivariate statistical analysis including PCA analysis and OPLS-DA analysis were performed based on these metabolites. PCA analysis was utilized to explore the changes of the overall metabolic profiles by visualizing cluster and reducing the dimension of complex data [13]. The PCA score plot (3D) showed a distinct separation between the SHR-NCW and SHR-Untreated groups (Fig.…”
Section: Multivariate Statistical Analysis Of Kidney Metabolic Profilesmentioning
confidence: 99%
“…However, very limited researches have been reported on the application of metabolomics in investigating the mechanism of ACE inhibitory peptides. The untargeted serum metabolomics analysis carried out by Yu et al demonstrated that a total of 8 potential serum biomarkers were identified in SHRs after intervention with peptide QIGLF and peptide QIGLF might lower blood pressure by improving endothelial dysfunction [13]. Manoharan et al found that the levels of serum metabolites associated with renin-angiotensin system were significantly changed in SHRs after administration with peptide GVR [14].…”
Section: Introductionmentioning
confidence: 99%